The dame in the kimono : Hollywood, censorship, and the production code - Leff, Leonard J.; Simmons, Jerold, 1941- (University Press of Kentucky, 2001)
The new edition of this seminal work takes the story of the Production Code and motion picture censorship into the present, including the creation of the PG-13 and NC-17 ratings in the 1990s.